Real time Ultrasound Guided Percutaneous Native Renal Biopsy- Approach, Safety and Complications - Pant, Ashok Raj; Rauniyar, R.K.; Gupta, M.K.; Bartaula, B.; Subedi, M.; Dhakal, S. (Journal of BP Koirala Institute of Health Sciences, 2018)
Introduction: Ultrasound guided percutaneous renal biopsy (PRB) is a relatively safe procedure; however, life threatening complications may occur even in current practice. There has been considerable decrease in the risk associated with percutaneous renal biopsy (PRB) in last few decades due to modifications in the biopsy needle as well as advancement in the image guidance. Objectives: To determine the complications and efficacy and to determine relationship between the clinical/ laboratory findings with rate of complications. Material and methods: We retrospectively evaluated hospital records of total of 150 patients who underwent PRB between September 2014 to August 2016 in the department of Radio diagnosis and Imaging at B. P. Koirala Institute of Health Sciences (BPKIHS), Dharan, Nepal. The renal biopsies had been performed with the current automated biopsy gun under real-time ultrasound guidance. The collected data were entered in MS excel. Results: In the total 150 patients, the efficacy (adequacy of the sample) of the procedure was 97.3%. The complications were seen in 13 cases (8.6 %). Five out of these complications were major with 2 cases requiring blood transfusion. The univariate analysis demonstrated the risk factors for developing complications as follows: low platelet count, prolong PT/INR, elevated Blood Urea Nitrogen (BUN) and serum creatinine value and elevated systolic and diastolic blood pressure. However, elevated diastolic blood pressure and prolong PT/INR were associated with complications in multivariate logistic regression analysis. Conclusions: The percutaneous renal biopsy is the safe and efficacious procedure to establish histological diagnosis of renal parenchymal disease.